H. Reinder Reinders et al. The City of New Halos and its Southeast Gate. pp. 205, with col. ills. 2014. Groningen: Barkhuis (Groningen Archaeological Studies Vol. 27). ISBN 978-9-49143-168-5, hardcover €70. - Farinetti, Emeri (Journal of Greek Archaeology, 2020)
The existence of openings in the city wall determines the very essence of the city: gates are both the weakest and the strongest spots of a town, and they form the connection with the outside world, affecting the character of the inner space. In this volume, the description itself of the city of New Halos, the examination of its urban layout and its surroundings, moves towards, and at the same time culminates in, the detailed description of one of its gates, the Southeast Gate, systematically excavated during the period 1995-2006.